SAT0164 Association between flare and radiographic progression in patients with rheumatoid arthritis. (15th June 2017) - Smolen, JS; Jones, H; Mahgoub, E; Pedersen, R; Marshall, L
Abstract : Background: Biologic therapy has improved RA management, enabling some patients to achieve remission. Many clinicians decrease the biologic dose for patients in low disease activity (LDA) or remission. However, it is unclear which patients may flare and if flare contributes to radiographic progression. Objectives: To assess whether patients who flared had a higher incidence of radiographic progression, and to compare patients with and without flares. Methods: PRESERVE (ClinicalTrials.gov: NCT00565409 ) was a 2-period trial in patients with moderate RA despite MTX. Period 1 was open-label, single treatment induction with etanercept (ETN) 50mg+MTX weekly (QW) for 36 wks. Patients in LDA or remission (disease activity score for 28 joints [DAS28] ≤3.2) during wks 12 to 36 continued to Period 2, the randomized, double-blind phase to evaluate maintenance of LDA/remission. Patients were randomized to ETN 50mg+MTX QW, ETN 25mg+MTX QW, or placebo+MTX QW to wk 88. This post hoc analysis evaluated flare and radiographic progression at wk 88. Flare was defined 2 ways: 1) loss of LDA with/without DAS28 change of 0.6; and 2) relapse (DAS28>5.1 or DAS28>3.2 at ≥2 time points). Radiographic progression was evaluated according to 4 levels of stringency: 1) minimally clinically important difference (modified total Sharp score [mTSS] change ≥5); 2) smallest detectable difference (mTSS change ≥2.3); 3) mTSS change ≥0.5; and 4) mTSS change >0. Baseline (BL) characteristics were compared for patients with vs without flare, defined as loss of LDA and DAS28 change of 0.6. Analysis of covariance and chi-square test compared continuous and categorical outcomes, respectively. Results: Age, race, BMI, and disease duration did not differ significantly for flare vs non-flare, total N=531. BL DAS28 was higher for flare vs non-flare: mean (SD) 4.37 (0.45) vs 4.27 (0.45), p =0.046. Other BL disease characteristics were similar between groups. With flare defined as relapse, significantly more flare than non-flare patients showed all 4 degrees of radiographic progression (table). With flare defined as LDA loss with/without DAS28 change of 0.6, radiographic progression did not differ significantly between groups, but numerically more patients with flare progressed. This was the trend for all treatments; the numbers were too small to analyze. Numerically more placebo patients progressed, regardless of flare status or progression category (data not shown). Conclusions: Using relapse as a rigorous definition of flare, radiographic progression occurs in significantly more flare than non-flare patients, demonstrating that it is a consequence of flare following biologic withdrawal. Disclosure of Interest: J. Smolen Grant/research support from: Abbvie, Janssen, Lilly, MSD, Pfizer, Roche, Consultant for: Abbvie, Amgen, Astra-Zeneca, Astro, Celgene, Celtrion, Glaxo, ILTOO, Janssen, Lilly, Medimmune, MSD, Novartis-Sandoz, Pfizer, Roche, Samsung, Sanofi, UCB, Speakers bureau: Abbvie, Amgen, Astra-Zeneca, Astro, Celgene, Celtrion, Glaxo, ILTOO, Janssen, Lilly, Medimmune, MSD, Novartis-Sandoz, Pfizer, Roche, Samsung, Sanofi, UCB, H. Jones Shareholder of: Pfizer, Employee of: Pfizer, E. Mahgoub Shareholder of: Pfizer, Employee of: Pfizer, R. Pedersen Shareholder of: Pfizer, Employee of: Pfizer, L. Marshall Shareholder of: Pfizer, Employee of: Pfizer